Acute and Subacute Toxicity Study of Methanolic Extract of ceiba pentandra (Linn.) Gaertn. on Rats - Gandhare, B.; Kavimani, S.; Rajkapoor, B. (Journal of Scientific Research, 2013)
The purpose of toxicity testing is to provide adequate database to make decisions concerning the toxicology properties of chemical and commercial products. In some situations, the purpose is to decide whether a material will be safe. Under the conditions of expected use in other situations, the objective is to establish the safe limits in condition of use. The methanolic extract of ceiba pentandra was evaluated for acute and subacute toxicity in adult Wistar rats. For the study of acute toxicity, the methanol extract of roots of C. pentandra (MCP) was given separately in various doses (50, 500, 1000, 2000 mg/kg) by oral route. The results showed no signs of toxicity such as general behavior change, mortality, or change in gross appearance of internal organs. Subacute toxicity was studied by daily oral doses 100, 400 and 750 mg/kg (low dose, intermediate dose and high dose) orally for 28 days. The results showed no abnormalities in treated groups as compared to the controls. Although significantly different, all of the values were within normal limits. Neither gross abnormalities nor histopathological changes were observed. Keywords: Acute toxicity; Subacute toxicity; ceiba pentandra. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.11800 J. Sci. Res. 5 (2), 315-324 (2013)